Factors influencing marginal bone loss at a hydrophilic implant design placed with or without GBR procedures: A 5‐year retrospective study. (21st August 2019) - Zumstein, Thomas; Schütz, Silvio; Sahlin, Herman; Sennerby, Lars
Abstract: Background: Ongoing marginal bone loss is a threat to the longevity of implant‐supported prostheses. Aim: The aim of the present study was to retrospectively evaluate the survival rate and factors affecting marginal bone levels at a hydrophilic implant design after 5 years in function. Materials and Methods: The study group consisted of 51 consecutive patients previously treated with 159 hydrophilic implants (Neoss Straight Proactive implants) and scheduled for annual check‐ups with clinical and radiographic examinations during 5 years. Data were compiled for the entire study population as well as for two subgroups: one where guided bone regeneration (GBR) was performed (91 implants) and the other where no GBR procedures (68 implants) were performed. Marginal bone levels were measured from peri‐apical radiographs taken at placement and annual follow‐ups. Statistical analyses were applied to evaluate the effect of different factors on marginal bone remodeling. Results: Two implant failures, one from each subgroup, occurred during the first year of function resulting in an overall cumulative survival rate (CSR) of 98.7% after 5 years of loading. The mean marginal bone loss amounted to 0.7 ± 0.7 mm after 1 year and 0.8 ± 0.6 mm after 5 years. No implants showed more than 3 mm bone loss after 5 years. Age, gender, implant position, biotype, implant diameter, implant length, indication, surgical/loading protocol, and ISQ at prosthesis delivery were found to affect bone remodeling. No significant differences or correlations were seen for smoking, jaw, bone quantity, bone quality, GBR, sinus lift, and ISQ at implant placement. Conclusions: The present implant design performed well with few failures and minimal marginal bone loss after 5 years of loading. Marginal bone remodeling at implants is a complex phenomenon, which is affected by many patient‐, procedure‐, and implant‐related factors that need to be further investigated.